A Review of Gamma Oscillations in Healthy Subjects and in Cognitive Impairment - BAŞAR, EROL (Elsevier Science Bv, Po Box 211, 1000 Ae Amsterdam, Netherlands, 2013)
This review describes a wide range of functional correlates of gamma oscillations in whole-brain work, in neuroethology, sensory-cognitive dynamics, emotion, and cognitive impairment. This survey opens a new window towards understanding the brain's gamma activity. Gamma responses are selectively distributed in the whole brain, and do not reflect only a unique, specific function of the nervous system. Sensory responses from cortex, thalamus, hippocampus, and reticular formations in animal and human brains, and also cognitive responses, were described by several authors. According to reviewed results, it becomes obvious that cognitive disorders, and medication which influence the transmitter release change entirely the understanding of the big picture in cognitive processes. Gamma activity is evoked or induced by different sensory stimuli or cognitive tasks. Thus, it is argued that gamma-band synchronization is an elementary and fundamental process in whole-brain operation. In conclusion, reasoning and suggestions for understanding gamma activity are highlighted. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: gamma oscillations; cognition; bipolar disorders; schizophrenia; memory; gam salınımları; biliş; bipolar bozukluklar; şizofreni; bellek